Involvement of Autophagy in Oncogenic K-Ras-induced Malignant Cell Transformation - Kim, Min-Jung (American Society for Biochemistry and Molecular Biology, 2011)
Autophagy has recently been implicated in both the prevention and progression of cancer. However, the molecular basis for the relationship between autophagy induction and the initial acquisition of malignancy is currently unknown. Here, we provide the first evidence that autophagy is essential for oncogenic K-Ras (K-Ras(V12))-induced malignant cell transformation. Retroviral expression of K-Ras(V12) induced autophagic vacuole formation and malignant transformation in human breast epithelial cells. Interestingly, pharmacological inhibition of autophagy completely blocked K-Ras(V12)-induced, anchorage-independent cell growth on soft agar. Both mRNA and protein levels of ATG5 and ATG7 (autophagy-specific genes 5 and 7, respectively) were increased in cells overexpressing K-Ras(V12). Targeted suppression of ATG5 or ATG7 expression by short hairpin (sh) RNA inhibited cell growth on soft agar and tumor formation in nude mice. Moreover, inhibition of reactive oxygen species (ROS) with antioxidants clearly attenuated K-Ras(V12)-induced ATG5 and ATG7 induction, autophagy, and malignant cell transformation. MAPK pathway components were activated in cells overexpressing K-Ras(V12), and inhibition of JNK blunted induction of ATG5 and ATG7 and subsequent autophagy. In addition, pretreatment with antioxidants completely inhibited K-Ras(V12)-induced JNK activation. Our results provide novel evidence that autophagy is critically involved in malignant transformation by oncogenic K-Ras and show that reactive oxygen species-mediated JNK activation plays a causal role in autophagy induction through up-regulation of ATG5 and ATG7.